Pelatihan Penggunaan Tools AI di Gereja GKPB Jemaat Efrata Buduk - I Nyoman Bernadus; Prastyadi Wibawa Rahayu; I Made Dwi Ardiada; Gabriel Firsta Adnyana; Putu Wida Gunawan; Gerson Feoh (Politeknik Piksi Ganesha Indonesia, 2025)
Understanding of the use of AI, especially ChatGPT, is still relatively minimal in the GKPB Efrata Buduk Church. This is a special concern, considering the great potential of AI in supporting church services, from helping to prepare sermon materials, to managing administration. The purpose of this training is to improve the understanding and skills of the assembly and congregation in utilizing AI, so that this technology can be used optimally to support church activities, the methods used range from socialization, training, mentoring and evaluation as well as compiling final reports. The conclusion obtained is that there has been an increase in knowledge of the use of AI Tools from the results of the Pre-Test which never used AI Tools, after the training the participants understood its use and in the future wanted to use AI Tools to assist in Church activities. Keywords: ChatGPT, Training, Usage, Church